Ketaksaan Bahasa Sikka Dialek Sikka Krowe pada Masyarakat Desa Tana Duen Kecamatan Kangae Kabupaten Sikka - Monika Mayesha Ester; Yosef Demon; Dominika Dhapa (Medan Resource Center, 2022)
The problems raised ini this study are (1) how is the ambiguity of the Sikka dialect of Sikka Krowe in the Tana Duen village community, Kangae sub-district, Sikka districth (2) what is the meaning of ambiguity in the Sikka Krowe dialect Sikka language in the Tana Duen village community, Kangae sub-district, Sikka district. As for the purpose of this research is qualitative research. Thr purpose of the approach is to describe of the data directly in the fielf. The theory used in this research is semantic theory. Based on the resullts of the researrch on the ambiguity of the Sikka dialect of Sikka Krowe language in the Tana Duen village community, Kangar District, Sikka regency, there are 3 ambiguities, namely ambiguity at the phonetic level, grammatical level, and lexical level.